The inhibitory effect of human umbilical cord mesenchymal stem cells expressing anti-HAAH scFv-sTRAIL fusion protein on glioma - Xue, Tian; Wang, Xiaolin; Ru, Jing; Zhang, Lixing; Yin, Huancai (Frontiers in Bioengineering and Biotechnology, 2022)
Glioma is the most common primary intracranial tumor. The recurrence rate of glioma is high, and the side effects of treatment are serious. As a new type of drug or gene delivery cell carrier, human umbilical cord mesenchyreal stem cells (hucMSCs) present unique characteristics. In our study, we investigated the effect of hucMSCs expressing anti-HAAH scFv-sTRAIL fusion protein on glioma. The lipid droplets appeared in hucMSCs after adipogenic differentiation induction. The calcium nodules appeared in hucMSCs after osteogenic differentiation induction. The isolated hucMSCs showed expressions of CD105, CD90 and CD73, and no expression of CD34, CD19 and CD45. Compared with the LV-NC group, sTRAIL expressions in the cell culture supernatant and cells were obviously increased in the LV-scFv-sTRAIL group. LV-scFv-sTRAIL had no obvious effect on the hucMSCs biomarkers expressions. LV-scFv-sTRAIL significantly improved the migration of hucMSCs toward U87G. U87G proliferation was significantly inhibited by hucMSCs infected with LV-scFv-sTRAIL. The U87G apoptosis was markedly induced by hucMSCs infected with LV-scFv-sTRAIL. In-vivo experiments demonstrated that the glioma tumor weight and volume were significantly inhibited by hucMSCs infected with LV-scFv-sTRAIL. Cell apoptosis in xenograft tumor was significantly elavated by hucMSCs infected with LV-scFv-sTRAIL. The hucMSCs infected with LV-scFv-sTRAIL gain the capability to target and kill gliomas cells in vitro and in vivo.